COGNITIVE BEHAVIOUR THERAPY PADA SKIZOFRENIA - Ira Aini Dania (Fakultas Keperawatan Institut Kesehatan Deli Husada, 2019)
Cognitive Behaviour Therapy (CBT) in the first schizophrenia was developed to provide additional treatment forresidual symptoms arising and also used in patients experiencing anxiety and depression. Rapid progress willgain from the CBT session when trust has built-in several meeting sessions through increasing mutualunderstanding and doing reality tests as in CBT, need to develop. The stages do run slowly following thecognitive deficits and ongoing symptoms such as hallucinations or sedentary. This article discusses the historyand development of cognitive behavior therapy, depictions, procedures, and techniques of CBT and its processesin the treatment of schizophrenia.